Peran Petani Perempuan dalam Usahatani Kopi dan Kontribusinya Terhadap Pendapatan Keluarga di Kelompok Tani Girisenang, Cilengkrang, Jawa Barat - Sihombing, Elisabeth Veronica; Qanti, Sara Ratna; Budiman, Muhammad Arief; Ernah, Ernah (Universitas Galuh, 2026)
Women play an important role in agriculture by increasing production by 20-30% in developing countries, including Indonesia. However, in recent years, the production of coffee from the Girisenang Farmers Group has decreased significantly. This study aims to determine the role played by female coffee farmers from the Girisenang Farmers Group in coffee farming activities and household activities, and to determine how much their income contributes to their family income. This study was located in Legok Nyenang, Girimekar Village, Cilengkrang, Bandung Regency, West Java. This study used a descriptive quantitative research design and survey method, with 40 female coffee farmers from the Girisenang Farmers Group as respondents. Data analysis used the Harvard Model gender analysis, work time analysis, and income contribution analysis. The results of this study indicate that female farmers have an important role in coffee farming activities which is manifested in their role together with their husbands, but are still limited in decision making. Female farmers also have a very large role in household activities. Last, the contribution of female farmers' income to their family income is included in the moderate category.